Analysis of Risky Sexual Behavior Among Adolescents in Langsa - Sherly Wardana; Razia Begum Suroyo; Ramadhani Syafitri Nasution (PROMOTOR, 2026)
The Indonesian Adolescent Reproductive Health Survey reported that 33.2% of male adolescents and 9.1% of female adolescents had engaged in intimate touching, 53.8% of males and 36.7% of females had kissed, and 6.1% of males and 1.5% of females aged 15–19 years had experienced premarital sexual intercourse. This study aimed to analyze the factors influencing risky sexual behavior among adolescents in Langsa. This study employed a mixed-methods design using an explanatory sequential approach. The quantitative phase involved 143 adolescents selected through total sampling. The qualitative phase included nine informants: four adolescents, one vice principal for student affairs, one guidance and counseling teacher, and three parents. Quantitative data were analyzed using multiple logistic regression, while qualitative data were analyzed through data reduction, data display, and conclusion drawing. The results of the chi-square test showed that attitude (p = 0.001), peer influence (p = 0.000), family role (p = 0.006), social media use (p = 0.000), and self-control (p = 0.003) were significantly associated with risky sexual behavior (p < 0.05). The most influential factor was social media use, with an odds ratio (OR) of 14.356. Qualitative findings supported these results, indicating that exposure to social media strongly influenced adolescents’ experiences and contributed to risky sexual behavior. In conclusion, attitude, peer influence, family role, social media use, and self-control significantly affect risky sexual behavior among adolescents in Langsa City. It is recommended that adolescents be more selective in their use of social media and strengthen their understanding of personal boundaries. Parents should improve communication and supervision, while schools should enhance reproductive health education through regular programs and counseling involving health professionals.